Marketing Strategy in Increasing Sales of D'besto Products - Trilaksono, Agung; Afifudin, Zen; Digdowiseiso , Kumba (CV ODIS, 2024)
Fried Chicken is a type of fast food that is popular with Indonesian people. The high public interest in fried chicken creates promising business opportunities for business people. D'Besto is known to the public for its various menu variants, easy to find and affordable prices. This research is based on the company's strategy to increase sales by implementing various methods to generate and increase profits. Companies face various obstacles in maintaining and improving their business by overcoming their shortcomings, so that they can continue to innovate in development in order to maintain their characteristics, and to increasingly gain advantages over competitors. This research aims to determine the marketing strategy carried out by D'Besto in marketing and increasing sales of its Fried Chicken products. The research method used is qualitative with a case study approach to the D'Besto business. Data were collected using in-depth interviews with 2 informants consisting of 1 D'Besto owner and 1 D'Besto Engagement Manager employee. This research aims to determine the advantages and disadvantages of D'Besto's marketing strategy. This research uses a qualitative research approach. The data sources used are primary data and secondary data. Data collection techniques through interviews, observation and documentation. As well as using data analysis techniques and checking the validity of the findings. The research results show that marketing strategies to increase sales at D'Besto can be achieved by implementing the Marketing Mix 7P (Product, Price, Place, Promotion, People, Process, Physical Evidence) and SWOT Analysis (Strengths, Weaknesses, Opportunities, and Threats).